THE MEANING AND FORM OF VERB TENSES IN ENGLISH AND UZBEK - Qosimova Munisa Feruz qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper investigates the intricate systems of verb tenses in English and Uzbek, exploring the similarities and differences in how these two languages express time and aspect. Through a comparative analysis, the study examines the morphological and syntactic structures employed by each language to convey temporal and aspectual information. Investigating the role of aspect in both languages, specifically focusing on how perfective, imperfective, and progressive aspects are expressed and how they interact with tense to create a more comprehensive understanding of temporal reference. Examining the morphological devices, such as affixes and auxiliaries, used by each language to convey tense and aspect. This includes a comparison of the regularity and complexity of these morphological systems.